OBSERVATION OF INTERFACIAL PLASMONS ON MBE-GROWN GAAS BY HIGH-RESOLUTION ELECTRON-ENERGY-LOSS SPECTROSCOPY - Graygrychowski, Z; Stradling, R; Egdell, R; Dobson, P; Joyce, B; Woodbridge, K (1986)
Plasmons at the interface between heavily-doped MBE grown n-type GaAs (n ≅ 4 × 1018 cm-3) and a surface depletion layer about 200 Å thick have been observed by HREELS. The variation of the plasmon frequency and intensity with exciting beam energy are discussed within the framework of a simple two layer model. © 1986.